ChemInform Abstract: Intermolecular Cyclization of N‐Methylanilines and Maleimides to Tetrahydroquinolines via K2S2O8 Promoted C(sp3)—H Activation. Issue 29 (June 2016) - Yadav, Arvind K.; Yadav, Lal Dhar S.
Abstract: An efficient and straightforward synthesis of tricyclic compounds incorporating biologically relevant tetrahydroquinoline core using K2 S2 O8 as a cheap radical initiator is reported.